Dynamics of the O + H2+ → OH+ + H, OH + H+ proton and hydrogen atom transfer reactions on the two lowest potential energy surfaces. Issue 5 (19th January 2017) - Martínez, Rodrigo; Paniagua, Miguel; Mayneris-Perxachs, Jordi; Gamallo, Pablo; González, Miguel
Abstract : The dynamics of the title reaction was studied using mainly the quasiclassical trajectory (QCT) method on the ground 1 2 A′′ (OH + channel) and first excited 1 2 A′ (OH channel) potential energy surfaces (PESs) employing ab initio analytical representations of the PESs developed by us. Abstract : The dynamics of the title reaction was studied using mainly the quasiclassical trajectory (QCT) method on the ground 1 2 A′′ (OH + channel) and first excited 1 2 A′ (OH channel) potential energy surfaces (PESs) employing ab initio analytical representations of the PESs developed by us. Both PESs correspond to exoergic reactions, are barrierless and present a deep minimum along the minimum energy path (MEP). Some extra calculations (cross sections) were also performed with the time dependent quantum real wave packet method at the centrifugal sudden level (RWP-CS method). A broad set of properties as a function of collision energy ( E col ≤ 0.5 eV) was considered using the QCT method: cross sections, average fractions of energy, product rovibrational distributions, two- and three-vector properties, and the microscopic mechanisms analyzing their influence on the dynamics. The proton transfer channel dominates the reactivity of the system and significant differences between the two reaction channels are found for the vibrational distributions and microscopic mechanisms. The results were interpreted according to the properties of the ground and excited PESs. Moreover, the QCT and RWP-CS cross sections are in rather good agreement for both reaction channels. We hope that this study will encourage the experimentalists to investigate the dynamics of this interesting but scarcely studied system, whose two lowest PESs include the ground and first excited electronic states of the H2 O + cation.